The potential of prophecy: Māori prophetism and the community development - Rangiwai, Byron (Te Kaharoa, 2012)
In nineteenth century Aotearoa-New Zealand prophet-leaders rose up to challenge the hegemony of imperialism by melding Indigenous epistemologies with introduced ones. In this sense Māori prophets blended the old world with the new as a means of both cultural survival and resistance against colonialism. One such nineteenth century prophet-leader was Te Kooti Arikirangi Te Turuki (c.1832-c.1891) who blended traditional Māori knowledge with biblical ideas, knowing that for Māori traditions to survive, they needed to be synthesised with introduced ideas, thus avoiding complete obliteration. Te Kooti gave many prophecies, some of which were delivered as riddles rich with metaphor and mystery. As a result of severe land loss in the Rangitaiki Valley in the Bay of Plenty of New Zealand at the hands of a Pākehā (European) man, Te Kooti issued a prophecy of promise and restoration in which the future return of the land was guaranteed. Within the Māori sub-tribes of Patuheuheu and Ngāti Haka, to whom this prophecy was given, Te Kooti’s revelations gained new meaning; his words are continually being transported from history into contemporary times. This paper will explore and analyse the ways in which this prophecy is being used today within the Patuheuheu and Ngāti Haka sub-tribes and how this research is using this local knowledge to build a culturally appropriate, transformative community praxis and development model.